Effect of two antagonists on damping off disease of tomato - K. RAJAPPAN; G. AMUTHA, S.K. MANORANJITHAM, V. PRAKASAM (Indian Phytopathology, 2002)
Soil application of Trichoderma viride and Pseudomonas fluorescens effectively controlled the pre-emergence and post-emergence damping off of tomato caused by Pythium aphanidermatum under pot culture experiments. Talc based formulation of antagonists significantly reduced the soil population of Pythium and increased the shoot length, root length and dry matter production of tomato seedlings. The individual and combined effect of these two biocontrol agents was on par with that of copper oxychloride.